Biblical archaeology from the ground down - Shanks, Hershel; Artzy, Michal, 1943-; Biblical Archaeology Society (Washington, D.C. : The Biblical Archaeology Society [distributor], 2003)
Join with the world's leading excavators as they dig, sift, and sort, removing centuries of sand and stone to bring the past to light.
Disc 1: Ashkelon / Lawrence Stager ; Hazor / Amnon Ben-Tor ; Jezreel / David Ussishkin ; Megiddo / Israel Finkelstein ; Tel Nami / Michal Artzy ; Tel Gezer / William Dever -- Disc 2: Solomon in his context--he's for real / Kenneth Kitchen ; Stratigraphy in geography, history...and archaeology / John Monson ; Seafaring in biblical times / Shelley Wachsmann ; Galilean archaeology and the historical Jesus quest / Douglas Edwards ; Locating the Herodian Temple: old and new theories in light of ancient literary evidence / James Tabor ; The relevance of biblical archaeology / Bernhard Anderson.
Title from label.
In container.
Writer, director, Hershel Shanks.
DVD.
Keywords: Bible -- Antiquities